Diagnostic and Prognostic Performance of the Modified Lumipulse pTau 181 Assay in Plasma for Alzheimer's Disease. (20th December 2022) - Wilson, Edward N.; Young, Christina B; Benitez, Javier A. Ramos; Vandijck, Manu; Swarovski, Michelle S.; Shahid, Marian; Corso, Nicole; Kennedy, Gabriel; Trelle, Alexandra N; Channappa, Divya; Belnap, Malia; Lind, Betty; et al.
Abstract: Background: Recent advances demonstrate utility in blood‐based phosphorylated tau (pTau) as a diagnostic biomarker for Alzheimer's disease (AD). While several platforms show high diagnostic and prognostic performance, most assays rely on antibody combinations that require long tau peptides for their detection. The Lumipulse G Plasma pTau 181 assay (Fujirebio) instead uses an antibody combination targeting epitopes proximal to Thr181 and therefore can detect shorter tau peptides. This allows for a wider array of expressed plasma pTau 181 peptides to be measured. Method: Plasma pTau 181 was measured in three cohorts using the modified Lumipulse G Plasma pTau 181 assay: cohort 1 included 269 cognitively unimpaired (CU), 109 mild cognitively impaired (MCI), and 80 AD participants from the Stanford Alzheimer's Disease Research Center (ADRC); cohort 2 included 192 CU from the Stanford Aging and Memory Study (SAMS); and cohort 3 a third, independent plasma cohort from the Yale University ADRC included 20 CU and 20 AD participants. Outcome measures included discriminative accuracy of the modified assay for clinical AD diagnosis, association with amyloid and tau pathology determined using CSF biomarkers or positron emission tomography (PET), and ability to predict longitudinal cognitive change. Result: Plasma pTau 181 showed robust clinical performance in differentiating AD from CU participants in cohort 1 (AUC = 0.934) and cohort 3 (AUC = 0.845). In cohort 1, the analyte associated with CSF pTau 181 (β=+0.543 and P <0.001), CSF Aβ42/Aβ40 ratio (β=‐0.349 and P <0.001), and amyloid‐PET global SUVRs (β=+0.494 and P <0.001). Associations between plasma P‐tau181 with CSF and PET biomarkers were significant when examined in Aβ+ and Aβ‐ groups separately. Plasma pTau181 was also found to associate with inferior temporal tau‐PET in the subset of CU in cohort 2 (N=35, β=+0.393 and P =0.016). Finally, in cohort 1 baseline plasma pTau 181 predicted change in MoCA over 2‐year follow‐up, controlling for clinical diagnosis, age, sex, and education (β=‐0.211 and P =0.009). Conclusion: The results across these 3 participant cohorts revealed the modified Lumipulse G pTau 181 assay discriminates AD pathology in clinical and preclinical AD, strongly associates with CSF and PET imaging in Aβ+ and Aβ‐ participants and predicts longitudinal cognitive decline.